2019
DOI: 10.1111/ppl.13023
|View full text |Cite
|
Sign up to set email alerts
|

Sodium hydrosulfide priming improves the response of photosynthesis to overnight frost and day high light in avocado (Persea americana Mill, cv. ‘Hass’)

Abstract: Radiation frost events, which have become more common in the Mediterranean Basin in recent years, inflict extensive damage to tropical/subtropical fruit crops. During radiation frost, sub‐zero temperatures are encountered in the dark, followed by high light during the subsequent clear‐sky day. One of the key processes affected by these conditions is photosynthesis, which, when significantly inhibited, leads to the enhanced accumulation of reactive oxygen species (ROS) and damage. The use of ‘chemical priming’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 54 publications
3
27
1
Order By: Relevance
“…The CO 2 -assimilation rate in the young avocado plants ranged between 5 and 8 μmol m −2 s −1 , similar to previously published results for young potted ‘Hass’ plants [ 22 , 23 ]. CO 2 assimilation was only significantly reduced at 49 °C and above, suggesting this as the temperature threshold for heat stress damage in young avocado plants.…”
Section: Discussionsupporting
confidence: 90%
“…The CO 2 -assimilation rate in the young avocado plants ranged between 5 and 8 μmol m −2 s −1 , similar to previously published results for young potted ‘Hass’ plants [ 22 , 23 ]. CO 2 assimilation was only significantly reduced at 49 °C and above, suggesting this as the temperature threshold for heat stress damage in young avocado plants.…”
Section: Discussionsupporting
confidence: 90%
“…When plants suffer from various abiotic stresses, the imbalance of redox state and the disorder of ion transport will largely restrict the photosynthesis of plants. Exogenous H 2 S can promote photosynthesis with a higher chlorophyll content in a variety of plants (Chen et al 2015b ; Liu et al 2020b ; Parveen et al 2017 ), even in lower algae (Dooley et al 2013b , 2015 ; Joshi et al 2020 ), suggesting that the promotion of H 2 S on plant photosynthesis appeared in a very early period of plant evolution to improve plant survival. Chen et al ( 2011 ) have revealed the role of H 2 S in photosynthesis in Spinacia oleracea .…”
Section: H 2 S Contributes To Plant Growth and Devmentioning
confidence: 99%
“…Muñoz-Vargas et al (2019) have noticed inhibition of NADP-malic enzyme activity by H 2 S and NO in sweet pepper. Furthermore, the role of H 2 S was examined in regulating photosynthesis under overnight frost and daytime high light in avocado (Joshi et al 2019). Finally, Kataria et al (2019) have reported crucial role of nitrate reductase-dependent production of NO in regulating magnetopriming-induced salt tolerance in soybean.…”
mentioning
confidence: 99%